Current evidence and biological plausibility linking periodontitis to atherosclerotic cardiovascular disease - Koichi Tabeta, DDS,PhD; Hiromasa Yoshie, DDS,PhD; Kazuhisa Yamazaki, DDS,PhD (Elsevier, 2014)
The relationship between poor oral health and systemic diseases has been increasingly recognized over the past two decades. Atherosclerosis is an important basal component of atherosclerotic cardiovascular disease (ACVD), which is the primary cause of death worldwide, including Japan. The accumulation of multiple individual epidemiological studies has paved the way for subsequent systematic reviews that have demonstrated that periodontitis can be considered as an emerging risk factor for ACVD. Although the causal mechanisms by which periodontitis accelerates ACVD have not been fully elucidated, plausible evidence regarding the inflammatory response due to inflammatory mediators and bacterial etiologies, and the recognition of altered lipid metabolism in patients with periodontitis suggest that infection with periodontopathic bacteria can influence atherogenesis in vitro and in vivo. Animal model studies have strengthened this evidence. However, there have been a lack of interventional studies that show the effects of periodontal treatment on the future risk of ACVD; this lack of evidence critically weakens the importance of the relationship between the two diseases. This review presents a summary of the current evidence and biological plausibility that link periodontitis to ACVD.